Transcriptome analysis of Burkitt lymphoma cells treated with anti-convulsant drugs that are inhibitors of Epstein-Barr virus lytic reactivation. - Kelly L Gorres; David M Reineke; George Miller (PLoS ONE, 2024)
Herpesviruses have two distinct life cycle stages, latency and lytic replication. Epstein-Barr virus (EBV), a gamma-herpesvirus, establishes latency in vivo and in cultured cells. Cell lines harboring latent EBV can be induced into the lytic cycle by treatment with chemical inducing agents. In the Burkitt lymphoma cell line HH514-16 the viral lytic cycle is triggered by butyrate, a histone deacetylase (HDAC) inhibitor. Butyrate also alters expression of thousands of cellular genes. However, valproic acid (VPA), another HDAC inhibitor with global effects on cellular gene expression blocks EBV lytic gene expression in Burkitt lymphoma cell lines. Valpromide (VPM), an amide derivative of VPA, is not an HDAC inhibitor, but like VPA blocks induction of the EBV lytic cycle. VPA and VPM are the first examples of inhibitors of initial stages of lytic reactivation. We compared the effects of VPA and VPM, alone and in combination with butyrate, on host cellular gene expression using whole transcriptome analysis (RNA-seq). Gene expression was analyzed 6 h after addition of the compounds, a time before the first EBV lytic transcripts are detected. The results address two alternative, yet possibly complementary, mechanisms for regulation of EBV lytic reactivation. First, cellular genes that were up- or down-regulated by butyrate, but no longer altered in the presence of VPA or VPM, represent genes that correlated with EBV lytic reactivation. Second, genes regulated similarly by VPA and VPM in the absence and presence of butyrate are candidates for suppressors of EBV reactivation. Two genes upregulated by the lytic cycle inhibitors, CHAC1 and SLC7A11, are related to redox status and the iron-dependent cell death pathway ferroptosis. This study generates new hypotheses for control of the latency to lytic cycle switch of EBV and provides the first description of effects of the anti-convulsant drug VPM on global human cellular gene expression.